2014
DOI: 10.1017/s0033291714000129
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of mental health-related stigma on help-seeking? A systematic review of quantitative and qualitative studies

Abstract: Background. Individuals often avoid or delay seeking professional help for mental health problems. Stigma may be a key deterrent to help-seeking but this has not been reviewed systematically. Our systematic review addressed the overarching question: What is the impact of mental health-related stigma on help-seeking for mental health problems? Subquestions were: (a) What is the size and direction of any association between stigma and help-seeking? (b) To what extent is stigma identified as a barrier to help-see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

99
1,722
11
55

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,348 publications
(1,887 citation statements)
references
References 54 publications
99
1,722
11
55
Order By: Relevance
“…These findings reflect that not all people in the community suffering from psychiatric symptoms present at psychiatric hospitals/clinics, particularly within mental health hospitals. Moreover, people with psychiatric illnesses, particularly illnesses with mild to moderate severity, may seek advice from non-mental-health professionals, most likely because of stigma and cultural beliefs 31,32 . A study among the visitors to a number of faith healing (FH) settings in Riyadh, Saudi Arabia observed that a high proportion of the FH visitors had diagnosable mental illnesses that were not treated medically 17 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings reflect that not all people in the community suffering from psychiatric symptoms present at psychiatric hospitals/clinics, particularly within mental health hospitals. Moreover, people with psychiatric illnesses, particularly illnesses with mild to moderate severity, may seek advice from non-mental-health professionals, most likely because of stigma and cultural beliefs 31,32 . A study among the visitors to a number of faith healing (FH) settings in Riyadh, Saudi Arabia observed that a high proportion of the FH visitors had diagnosable mental illnesses that were not treated medically 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Since Erving Goffman's (1963) seminal work on the topic, the volume of research on stigma has rapidly expanded, spawning multiple major review articles in the past two decades alone (Clement et al 2015;Corrigan, Druss, and Perlick 2014;Gulliver, Griffiths, and Christensen 2010;Link and Phelan 2001;Major and O'Brien 2005;Parcesepe and Cabassa 2013;Pescosolido and Martin 2015). This heightened attention is, in part, due to the important associations between stigma and the severity of mental illness symptoms (Andrade et al 2014;Brown 2017;Drapalski et al 2013), disclosure of conditions to friends, family, and healthcare professionals (Dew et al 2007;Donnelly 2017;Prior et al 2003), self-esteem (Corrigan 2004;Corrigan and Watson 2002;Corrigan, Watson, and Barr 2006), and treatment-seeking behavior (Clement et al 2015;Tsang, Fung, and Chung 2010;Vogel, Wade, and Haake 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This heightened attention is, in part, due to the important associations between stigma and the severity of mental illness symptoms (Andrade et al 2014;Brown 2017;Drapalski et al 2013), disclosure of conditions to friends, family, and healthcare professionals (Dew et al 2007;Donnelly 2017;Prior et al 2003), self-esteem (Corrigan 2004;Corrigan and Watson 2002;Corrigan, Watson, and Barr 2006), and treatment-seeking behavior (Clement et al 2015;Tsang, Fung, and Chung 2010;Vogel, Wade, and Haake 2006). While population estimates suggest that many individuals with symptoms of mental illness do not receive treatment or are undertreated Wang et al 2005Wang et al , 2007, scholars, healthcare providers, and other stakeholders hope that stigma reduction efforts will increase treatment-seeking behavior (Clair, Daniel, and Lamont 2016;Hatzenbuehler, Phelan, and Link 2013;Hunter et al 2017;Pilgrim and Rogers 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Self-stigma involves moving beyond awareness of public stigma to agreeing with it and applying it to oneself (Corrigan and O'Shaughnessy, 2007;Watson et al, 2007). When public stigma is internalized, it can lead to decreased hope, quality of life, self-esteem, and greater symptom severity, including depression (Hasson-Ohayon et al, 2014;Lipsey and Wilson, 2001;Staring et al, 2013), as well as reduced help-seeking (Clement et al, 2015).…”
Section: Introductionmentioning
confidence: 99%